HUBUNGAN ANTARA KEAKTIFAN BELAJAR DAN BIMBINGAN BELAJAR ORANG TUA DENGAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL SISWA KELAS V SD SE-GUGUS SULTANAGUNG KECAMATAN KARANGANYAR KABUPATEN PURBALINGGA - Wakhyu Sri Utari; AL Sugijanto (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
This study aimed to know (1) correlation between learning activeness with learning achievement of social science subject, (2) the correlation between parents’ learning guidance with learning achievement of social subject, (3) the correlation between learning activeness and parents’ learning guidance with learning achievement of social science subject. The type of this study was a quantitative research. The data collecting techniques used questionnaire and documentation. The data analysis techniques used descriptive technique and hypothesis testing used Product Moment and double regression with two predictors that were started by an independence test, a normality test, and a linearity test. This study shows that the correlation coefficient of each independent variable had a positive correlation with dependent variable. The score of = 0.26557 > = 0.1912, it means that learning activeness had a positive and significant correlation with learning achievement of social science subject. The score of = 0.30402 > = 0.1912, it means that parents’ learning guidance had a positive and significant correlation with learning achievement of social science subject. The study shows that there is a positive and significant correlation between learning activeness and parents’ learning guidance with learning achievement of social science subject (Fregresi = 8.66415 > Ftabel=3.0884). It can be concluded that learning activeness and parents’ learning guidance have a correlation with learning achievement of social science subject among the fifth grade students of state elementary schools of Sultan Agung in Karanganyar Purbalingga. The score of R2 is 0.14521, it means that learning activeness and parents’ learning guidance gives contribution 14.521% toward learning achievement of social science subject, while 85.479% is explained by other factors that are not analyzed in regression model.